Nomophobia: An emerging problem - Banerjee, Indrajit; Robinson, Jared; Kashyap, Abhishek; Sathian, Brijesh (Nepal Journal of Epidemiology, 2023)
The rapid rise of the use and the human race’s reliance on technological devices such as mobile phones in the 21st century has been the precipitant for nomophobia and the current usage of such devices is only on the incline. The global burden of nomophobia will continue to rise and it is therefore prudent that the public are better educated about nomophobia and their devices as well as the negatives side effects of the overuse thereof. Prevention through limiting screen time and self-control measures remains the best arsenal to curb the precipitation and development of nomophobia.